Delivering Structural Information on the Polar Face of Membrane‐Active Peptides: 19F‐NMR Labels with a Cationic Side Chain. Issue 47 (20th October 2016) - Michurin, Oleg M.; Afonin, Sergii; Berditsch, Marina; Daniliuc, Constantin G.; Ulrich, Anne S.; Komarov, Igor V.; Radchenko, Dmytro S.
Abstract: Conformationally constrained non‐racemizing trifluoromethyl‐substituted lysine isosteres [( E )‐ and ( Z )‐TCBLys] with charged side chains are presented as a new type of 19 F‐NMR labels for peptide studies. Design of the labels, their synthesis, incorporation into peptides and experimental demonstration of their application for solid state NMR studies of membrane‐active peptides are described. A series of fluorine‐labeled analogues of the helical amphipathic antimicrobial peptide PGLa(Nle) was obtained, in which different lysine residues in the original peptide sequence were replaced, one at a time, by either ( E )‐ or ( Z )‐TCBLys. Antimicrobial activities of the synthesized analogues were practically the same as those of the parent peptide. The structural and orientational parameters of the helical PGLa(Nle) peptide in model bilayers, as determined using the novel labels confirmed and refined the previously known structure. ( E )‐ and ( Z )‐TCBLys, as a set of cationic 19 F‐NMR labels, were shown to deliver structural information about the charged face of amphipathic peptides by solid state 19 F‐NMR, previously inaccessible by this method. Abstract : Illuminating the "dark side" : A cyclobutane‐based α‐amino acid was designed as the first 19 F‐NMR label carrying a charged side chain. Two diastereomers of the amino acid were used to obtain solid‐state NMR constraints for the previously inaccessible cationic face of a membrane‐embedded peptide PGLa(Nle). The label showed similarity to lysine, allowing its use in NMR studies of lysine‐rich peptides in membranes.